Spatial characterisation of non-timber forest products markets in the humid forest zone of Cameroon - Ruíz Pérez, M.; Ndoye, O.; Eyebe, A.; Puntodewo, A. (2000)
The paper analyses the structure of non-timber forest products (NTFP) markets in the humid forest zone (HFZ) of Cameroon from a spatial perspective. A characterisation of 25 markets based on a set of products, traders, and market place attributes was produced. The combination of the attributes size and self-sufficiency results in four main types of markets (national, provincial, local and frontier), whereas clustering based on all the attributes clearly distinguishes the northern and southern areas of the HFZ, and an urban-rural, core-periphery relationship within each area. This separation reflects different product specialisations and diversity, as well as market size. Dacryodes and Gnetum predominate in the northern markets, which tend to be larger, whereas Garcinia lucida, G. Kola and Irvingia are relatively more abundant in the southern markets. In general, larger markets are more diversified and their traders are more specialised than the smaller ones. There are also differences in product storage time, distance from source of products, level of taxation, and transportation problems. The need to understand the multiple, non-linear interactions among these factors is stressed.